ESPERANTO AS SUCCESSFUL PROJECT OF AN INTERNATIONAL PLANNED LANGUAGE: 130 YEARS OF FUNCTIONING - Данилюк, Ніна (Current Issues of Foreign Philology, 2021)
The article is devoted to the international year of Ludwig Zamenhof, creator of Esperanto. The article deals with the Esperanto studies as a special branch of interlinguistics, with the biggest schools of esperantology of the 70s of the 20th–21st centuries: Moscow, Tartu and Budapest, and their famous representatives. Two ways of solving a problem of an international communication have been pointed out: the usage of ethnic languages and creation of planned languages of a priori and a posteriori types. The best known projects of international planned languages have been presented in the historical aspect starting with Antiquity and till present. Peculiar features of the phonetic, lexical and grammatical systems of Esperanto have been described and analyzed in the context of Esperanto being the most successful project of a planned language used in communication. The history of appearance and development of the Esperanto-movement in the world has been traced, international organizations, dealing with finding the solutions to the problems of verbal communication, have been named. A special attention has been paid to such topics as the achievements in the fields of studying and applying Esperanto in Ukraine, scientific and scientific-educational literature, translations of the texts of Ukrainian classical literature and folklore, scientific conferences, centers of Esperanto, special courses in Esperanto at the Lesya Ukrainka Eastern European National University, and Ukrainian organizations of Esperanto speakers.